Isolation and Identification of Pathogenic Bacteria from Fresh Fruits and Vegetable Sold in Market of Janakpurdham - Yadav, Nagendra Prasad; Yadav, Rakesh Kumar; Sah, Suveksha; Purbe, Harinarayan (MedS Alliance Journal of Medicine and Medical Sciences, 2024)
Introduction: Vegetable and fruits are highly nutritious palatable food. They are enriched sources of vitamins mineral and fibres. They are the essential part of our diet and used all over the world daily. They are perishable food. The microorganisms get easy access to enter inside it. They get contaminated with different types of bacteria, during cultivation, harvesting, processing, transportation, storage and consumption. Eating of bacterial contaminated fruits and vegetable can lead to severe problem to the community people. Bacterial contamination can cause degradation, loss of quality and potential health risk to the consumer. Materials and Methods: A total of 70 fresh fruits and vegetable were collected from different retailer of Janakpur metropolitan city, aseptically. Bacterial count and their identification were done in the microbiology lab in Model Multiple College Janakpur using different media and biochemical reagents. Results: Among them Pseudomonas species, Escherichia coli, Lactobacillus species, Staphylococcus species and salmonella species were the dominant bacteria. All of the fruits and vegetable were found heavily contaminated with bacteria. Bacterial count in different sample were found as in Guava count was 3.1 x104 CFU/ml, Apple was 4.3x104 CFU/ml, Tomato 6.2x104 CFU/ml, Cucumber 5.0x104 CFU/ml, carrot was 1.3x104 CFU/ml, Amara was 8.5x104 CFU/ml and Orange was 1.2x104 CFU/ml. Conclusions: The fruits and vegetable available in Janakpur market is highly contaminated and has a great risk for consumer health.